Nilai Tauhid dalam Dasa Darma Pramuka Menurut Perspektif Al-Qur’an - Nelvawita Nelvawita; Mochammad Novendri S. (Indonesian Journal of Scouting Studies, 2023)
The scouting movement does not only bring fun in joking, or like the accusations mentioned above, but this movement can be a reason for someone to know maturity, independence and the meaning of life. Scouting is not only in charge of human aspects and individual development, but also oversees the values ​​and essence of monotheism. So this study will examine how the values ​​of monotheism contained in Dasa Darma Pramuka according to the perspective of the Qur'an. This study will describe the value of monotheism in the Dasa Darma which is contained in the verses and interpretations of the Qur'an. This research is a literature research with a qualitative approach, with reference to primary and secondary data sources, then analyzed using the tahlili method in content analysis. Then the results obtained in this study that the value of monotheism in the Dasa Darma Scouts according to the perspective of the Qur'an is that it can be grouped into three broad lines, namely, firstly, by submitting and obeying God Almighty, which is a reflection in Surah al-Ikhlas verse 1 and Surah Al-Ikhlas verse 1 and Surah Al-Ikhlas. Taha Verse 14. The second is to be loyal as in Surah al-Mumtahanah verse 1 which is the actualization of the second, third and eighth Dasa Darma. The third is to be independent as in Surah al-Mumtahanah verse 4 as the implementation of the fifth and ninth tenets of Dharma.